2020
DOI: 10.3390/dj8040138
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Capability of Orthodontic Miniscrews: In Vitro Study

Abstract: The aims of this study were to assess the values and mechanical properties of insertion torque (IT) of steel miniscrews inserted in artificial bone blocks (Sawbones, Pacific Research Laboratories, Vashon, WA, USA) with different bone densities and to detect any scratches on the surface of the miniscrews after insertion. Forty self-drilling miniscrews (Leone S.p.A. ø 1.75 mm, L 8 mm) have been inserted into bone blocks that mimic different stability conditions (density: 20 PCF—pounds per cubic foot, 40 PCF, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…12 In the current literature the controversy remains regarding the effectiveness of in-vitro studies because of various limitations like the inability to reproduce oral environment, variation in bone density, and also various other hormonal and systemic conditions which will influence the outcome of the study. 13…”
Section: Introductionmentioning
confidence: 99%
“…12 In the current literature the controversy remains regarding the effectiveness of in-vitro studies because of various limitations like the inability to reproduce oral environment, variation in bone density, and also various other hormonal and systemic conditions which will influence the outcome of the study. 13…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic miniscrews also known as microscrews, mini-implants, or TADs (temporary anchoring devices) are intraoral devices specifically designed to be mounted within the bones of jaw in order to provide absolute anchorage [ 1 ]. Not needing patient's compliance, today, this technique is widely being used due to its high clinical efficacy, ease of insertion, low cost, and reduction of unwanted movement of other teeth [ 2 , 3 ]. Applications of these devices are mesialization, distalization, extrusion or intrusion of teeth, space opening, and, in some cases, alignment of midline or inclined plane [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) is a three-dimensional radiography which can accurately define the shape, morphology, and quantity of the maxillofacial bone [ 14 16 ]. This imaging modality presents cross-sectional views which can exactly indicate ridge height and width, concavity, angulation degree, the location and shape of tooth root, distance to anatomic landmarks, and bone density [ 3 , 6 ]. Using CBCT, Haddad et al indicated higher prevalence of miniscrew failure within the posterior maxilla due to reduced cortical bone thickness and suggested more apical insertion of miniscrew in order to access a denser buccolingual and palatal bone level [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) is a three dimensional radiography which can accurately de ne the shape, morphology and quantity of maxillofacial bone (13)(14)(15). This imaging modality presents cross sectional views which can exactly indicate ridge height and width, concavity, angulation degree, the location and shape of tooth root, distance to anatomic landmarks and bone density (3,6). Using CBCT, Haddad et al, indicated higher prevalence of mini-screw failure within posterior maxilla due to reduced cortical bone thickness, and suggested more apical insertion of mini-screw in order to access a denser bucco-lingual and palatal bone level.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic mini-screws also known as micro-screws, mini-implants or TADs (temporary anchoring devices) are intraoral devices speci cally designed to be mounted within the bones of jaw in order to provide absolute anchorage (1). Not needing patient's compliance, today, this technique is widely being used due to its high clinical e cacy, ease of insertion, low cost and reduction of unwanted movement of other teeth (2,3). Application of these devices are, mesialization, distalization, extrusion or intrusion of teeth, space opening and in some cases alignment of midline or inclined plane (4,5).…”
Section: Introductionmentioning
confidence: 99%